Expression of the transcription factor, PPAR in human monocytes - Jen, Ku Sheau (2004)
The peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily of transcription factor that mediate liganddependent transcriptional activation and repression. They regulate genes associated with lipid and glucose metabolism. Recent evidence suggests that PPARs may also act as a negative immunomodulator. To investigate the potential role of PPARa, y1 and y2 in regulating inflammation mediated by monocyte, the expression of PPARa, y1 and y2 in lipopolysaccharide (LPS)-activated and non-activated human monocytes was quantified. Monocytes secrete inflammatory cytokines such as interleukin (IL)-1 ~' IL-6 and tumor necrosis factor (TNF)-a in response to LPS. To verify stimulation of monocytes by LPS, various cytokines including granulocyte/macrophage colony-stimulating factor (GM-CSF), TN F-a, IL-1 ~' IL-6, IL-8 and transforming growth factor (TGF)J3 expression of LPS-activated and non-activated human monocytes was analyzed by using multiplex PCR and their expression is normalized against glyceraldehyde-3- phosphate dehydrogenase (GAPDH) expression. All these inflammatory cytokine expressions were increased in LPS-activated monocytes compared to non-activated monocytes. Measurement of the gene expression levels of PPARa, PPARy1 and PPARy2 in both LPS-activated and non-activated monocytes was carried out using Real-Time PCR analysis. The study showed that LPS induced expression of both PPARa and PPARy2 in isolated human monocytes with a preferential upregulation of PPARy2. The PPARy1 however was not expressed in both LPS-activated and non-activated